Trends in the incidence of testing for vitamin D deficiency in primary care in the UK: a retrospective analysis of The Health Improvement Network (THIN), 2005–2015. Issue 6 (4th June 2019) - Crowe, Francesca L; Jolly, Kate; MacArthur, Christine; Manaseki-Holland, Semira; Gittoes, Neil; Hewison, Martin; Scragg, Robert; Nirantharakumar, Krishnarajah
Abstract : Objective: To investigate trends in the incidence of testing for vitamin D deficiency and the prevalence of patients with circulating concentrations of 25-hydroxyvitamin D (25(OH)D) indicative of deficiency (<30 nmol/L) between 2005 and 2015. Design: Longitudinal analysis of electronic health records in The Health Improvement Network primary care database. Setting: UK primary care. Intervention: None. Participants: The analysis included 6 416 709 participants aged 18 years and older. Primary outcomes: Incidence of having a blood test for vitamin D deficiency between 2005 and 2015, the prevalence with blood 25(OH)D <30 nmol/L and the effects of age, ethnicity and socioeconomic status on these measures were assessed. Results: After a mean follow-up time of 5.4 (SD 3.7) years, there were 210 502 patients tested for vitamin D deficiency. The incidence of vitamin D testing rose from 0.29 per 1000 person-years at risk (PYAR) (95% CI 0.27 to 0.31) in 2005 to 16.1 per 1000 PYAR (95% CI 15.9 to 16.2) in 2015. Being female, older, non-white ethnicity and more economically deprived were all strongly associated with being tested. One-third (n=69 515) had 25(OH)D <30 nmol/L, but the per cent deficient among ethnic minority groups ranged from 43% among mixed ethnicity to 66% in Asians. Being male, younger and more economically deprived were also all associated with vitamin D deficiency (p<0.001). Conclusions: Testing for vitamin D deficiency increased over the past decade among adults in the UK. One-third of UK adults who had a vitamin D test performed in primary care were vitamin D deficient, and deficiency was much higher among ethnic minority patients. Future research should focus on strategies to ensure population intake of vitamin D, particularly in at-risk groups, meets recommendations to reduce the risk of deficiency and need for testing.